2018
DOI: 10.17503/agrivita.v40i1.1080
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Agricultural Drought in East Java Using Vegetation Health Index

Abstract: Drought is a natural hazard indicated by the decreasing of rainfall and water storage and impacting agricultural sector. Agricultural drought assessment has been used to monitor agricultural sustainability, particularly in East Java as national agricultural production center. Identification of drought characteristics -correlated with El Niño-Southern Oscillation, and agricultural impact on paddy fields and rice production using VHI (Vegetation Health Index) were conducted. VHI is produced by TCI (Temperature C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 11 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…The index originally used long-term data from the NOAA-AVHRR spacecraft and has recently been used with the Visible Infrared Imaging Radiometer Suite (VIIRS) spectral bands [55] as well. VHI has been applied on a regional scale in many areas around the world [56][57][58], but has also been proposed as a global drought index [55,[59][60][61]. Global coverage of the VHI is updated weekly on an official NOAA webpage (https://www.star.nesdis.noaa.gov/smcd/emb/vci/VH/vhbrowse.php).…”
Section: Relation To Lst-ndvi Modelsmentioning
confidence: 99%
“…The index originally used long-term data from the NOAA-AVHRR spacecraft and has recently been used with the Visible Infrared Imaging Radiometer Suite (VIIRS) spectral bands [55] as well. VHI has been applied on a regional scale in many areas around the world [56][57][58], but has also been proposed as a global drought index [55,[59][60][61]. Global coverage of the VHI is updated weekly on an official NOAA webpage (https://www.star.nesdis.noaa.gov/smcd/emb/vci/VH/vhbrowse.php).…”
Section: Relation To Lst-ndvi Modelsmentioning
confidence: 99%
“…The review can be used to analyze the strength and weaknesses of the method that could be improved in the next study. The monitoring of drought in Indonesia from remote sensing data has been carried out based on the VHI index with MODIS and TRMM images on an island-scale by Roswintiarti et al [63] and on provincial-scale by Amalo et al [64]. Dirgahayu [19] also use MODIS and TRMM images at the regency-scale based on a combination of drought types.…”
Section: Introductionmentioning
confidence: 99%
“…Climate related studies in Indonesia showed that extreme weather events are closely related to various natural disasters, such as drought (King et al, 2016;Surmaini et al, 2018;Taufik et al, 2020Taufik et al, , 2017, floods (Lestari and Dasanto, 2019;Narulita and Ningrum, 2018), and frost (Pradana et al, 2018a(Pradana et al, , 2018b. The disasters influence many sectors in Indonesia specially the agricultural sector (Amalo et al, 2017;Kim et al, 2019;Kuswanto et al, 2019;Lesk et al, 2016;Mulyaqin, 2020), which indirectly affect national economic conditions (Boer and Surmaini, 2020;Chatzopoulos et al, 2020). Extreme weather events mostly influence by regional climate variability, which periodically occur (Newman et al, 2018;Veitch et al, 2019).…”
Section: Introductionmentioning
confidence: 99%